Tranexamic Acid Administration in Adolescent Idiopathic Scoliosis Surgery Reduces % Total Blood Volume Loss. Issue 1 (April 2016) - Butler, Elissa; Garber, Tara; Ledonio, Charles; Polly, David W.; Cohn, Claudia
Introduction: Multilevel spinal fusion surgery for adolescent idiopathic scoliosis (AIS) is typically associated with significant blood loss. Antifibrinolytics such as tranexamic acid (TXA) have been proposed to reduce both blood loss and the need for transfusions. This study compares the blood loss and % total blood volume loss of AIS surgery patients with or without tranexamic acid. Materials and Methods: A retrospective comparative case-control study design was used to evaluate multilevel spinal fusion operations for AIS by a single surgeon from October 2011 to August 2014. Efficacy of TXA was evaluated by comparing mean estimated blood loss (EBL) and %TBV loss (calculated by Nadler's formula: males = 0.3669 * Ht m3 + 0.03219 * Wt kg + 0.6041; females = 0.3561 * Ht m3 + 0.03308 * Wt kg + 0.1833). Clinical factors including number of levels fused and length of operation were tested for correlation with % TBV loss. Results: From 2011 to 2014, 36 adolescents underwent AIS surgery (18 with and 18 without TXA). Mean age was 16 (±3) years and 86% (31/36) were female (controls 15/18 and TXA 16/18). There were no statistically significant mean differences between the ()TXA and (+)TXA groups in terms of the following: BMI (20.2 vs 22.2); estimated blood volume (3380 mL vs 3797 mL); levels fused (9.6 levels vs 10.5 levels); EBL (583 mL vs 474 mL) ( p  = 0.18); and EBL per level fused (61 mL/level vs 43 mL/level). Percent total blood volume loss and % TBV per level fused was significantly less in the TXA group (12% and 1%) compared with control group (17% and 2%) ( p  < 0.05). There was a moderate but significant direct correlation between number of levels fused ( p  = 0.024) and length of operation ( p  = 0.007) with % total blood volume loss. Conclusions: Administration of TXA during pediatric scoliosis surgery reduced % total blood volume loss by 30% compared with no TXA.